Althusser’s Criticism of ‘Piccolo Teatro’ - Ganvir, Anil Jaydeo (International Journal of Humanities and Education Development (IJHED), 2020)
This paper examines Althusser's theatre critique, which is to excavate his possible continuities around the theme. Althusser, regarded as a Marxist philosopher, also reveals his apprehension of the theatre criticism besides his critical encounters with Marxist reinterpretation. His critique of "Piccolo Teatro" incorporates and manifests various theoretical concepts and viewpoints useful for researching theorist and academics, particularly in theatre studies. Althusser's Piccolo Teatro -aesthetics proves to be the powerful testimony modern writers to follow and use to his critique with the uniqueness of his fresh approaches. The paper argues that Althusser in his ingenious critique of piccolo Teatro shares a dominant critique of theatre, setting up the new dramaturgy rules and ideas, besides reflecting diverse themes and approaches any of which can neither, in a closer observation, be the only underlying meaning as attempted by many.